2015
DOI: 10.1007/s10661-015-4710-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and loads of suspended sediment and trace element pollutants in a small semi-arid urban tributary, San Francisco Bay, California

Abstract: Water-quality policy documents throughout the world often identify urban stormwater as a large and controllable impact to sensitive ecosystems, yet there is often limited data to characterize concentrations and loads especially for rare and more difficult to quantify pollutants. In response, concentrations of suspended sediments and silver, mercury and selenium including speciation, and other trace elements were measured in dry and wet weather stormwater flow from a 100% urban watershed near San Francisco. Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 57 publications
4
23
2
Order By: Relevance
“…For example, median Cu and Zn concentrations in utility water in this study were 9.66 and 81.6 μg/L, substantially lower than the median concentrations in Paris stormwater of 55 and 270 μg/L, respectively (Zgheib et al 2012 ). Median Cu and Zn concentrations in utility vault water were comparable to the range of stormwater concentrations measured in a local study of urban runoff from Hayward, CA (McKee and Gilbreath 2015 ). That study, which focused on the smaller urban San Francisco Bay Area outfalls over 4 years (from water years 2007–2010) reported that Cu concentrations ranged from 2.3 to 50 μg/L and Zn concentrations ranged from 2.4 to 280 μg/L (McKee and Gilbreath 2015 ), which is similar to low and averaged utility vault water data.…”
Section: Discussionsupporting
confidence: 64%
“…For example, median Cu and Zn concentrations in utility water in this study were 9.66 and 81.6 μg/L, substantially lower than the median concentrations in Paris stormwater of 55 and 270 μg/L, respectively (Zgheib et al 2012 ). Median Cu and Zn concentrations in utility vault water were comparable to the range of stormwater concentrations measured in a local study of urban runoff from Hayward, CA (McKee and Gilbreath 2015 ). That study, which focused on the smaller urban San Francisco Bay Area outfalls over 4 years (from water years 2007–2010) reported that Cu concentrations ranged from 2.3 to 50 μg/L and Zn concentrations ranged from 2.4 to 280 μg/L (McKee and Gilbreath 2015 ), which is similar to low and averaged utility vault water data.…”
Section: Discussionsupporting
confidence: 64%
“…According to literature, the occurrence of metals such as Cd, Cr, Ni and Zn is not a surprise. The literature suggests a strong correlation between these metals and urban areas (GOMES et al, 2009;MINELLA, 2009;RIVARO et al, 2011;MCKEE;GILBREATH, 2015).…”
Section: Metal Concentration and Land Usementioning
confidence: 99%
“…Some authors found no significant variation in metals concentrations (ZGHEIB; MOILLERON; CHEBBO, 2011;GALLO et al, 2013), but others found significant variation (VALTANEN; SILLANPAA; SETALA, 2014;MCKEE;GILBREATH, 2015). The main potential sources of metals in sediments, especially in urbanized areas, are paved and unpaved streets, residential and industrial areas, also sewage discharges (SILVA; SIQUEIRA; LEANDRO, 2015;FRANZ et al, 2014;MIGUEL et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations